2010
DOI: 10.3742/opem.2010.10.2.066
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity studies on Trigonella foenum-graecum L. seeds used in spices and as a traditional remedy for diabetes

Abstract: SUMMARYAcute (24 h) and chronic (90 days) oral toxicity studies on the ethanol extract of Trigonella foenumgraecum Leguminosae (L.) seeds were carried out. Acute dosages were 0.5, 1.0 and 3 g/kg while chronic dosage was 100 mg/kg per day of the extract. All morphological, biochemical, haematological and spermatogenic changes, in addition to mortality, body weight changes and any change in vital organs were recorded. Histopathological investigations were done on vital organs. Growth arrest in the treated animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Information regarding galactomannan toxicity is almost negligible. In addition, fenugreek seeds have been consumed for many years without any reports of liver damage or histopathology involving vital organs such as the liver . However, it was also demonstrated that rats administered fenugreek seeds for 4 weeks at doses of 100, 150, or 200 mg kg –1 exhibited necrotic effects involving the liver and kidney tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding galactomannan toxicity is almost negligible. In addition, fenugreek seeds have been consumed for many years without any reports of liver damage or histopathology involving vital organs such as the liver . However, it was also demonstrated that rats administered fenugreek seeds for 4 weeks at doses of 100, 150, or 200 mg kg –1 exhibited necrotic effects involving the liver and kidney tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids help maintain liver function to keep warding off toxins caused by free radicals and drugs. Heavier organ weights indicate the occurrence of steatosis, which is fatty in liver cells which is seen as a symptom of toxic effects directly (Al-Ashban et al, 2010). Changes in heart weight are not always fatal (critical), because the liver is an organ that has tremendous growth capacity (Korani et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…[31][32][33] Two days after of alloxan injection, rats with plasma glucose levels of more than 200 mg/dl were included in the study and at this stage the blood glucose level of each rat was consider as basal value in each group. Treatment with plant extracts and standard drug was started after 48 h of alloxan injection.…”
Section: Experimental Methodsmentioning
confidence: 99%